16.2k views
1 vote
Find the solutions to the equation (-3y)(6y)+9=0​

User Yothenberg
by
5.4k points

1 Answer

3 votes

Answer:


y=\pm\text{ }i\sqrt{(1)/(2)}

Explanation:

So we first multiply out the parentheses, which turns out to be
-18y^2. So our equation is
-18y^2 + 9 = 0. We factor out a 9, which turns into
9(2y^2+1). So
2y^2+1=0. Solving, we have
y^2=-(1)/(2), and
y=\pm\text{ }i\sqrt{(1)/(2)}. I'm sorry everything is so messy, I hope you can still understand.

User Vatsal
by
5.4k points